The Impact of the Aussie Optimism Program on the Emotional Coping of 5- to 6-Year-Old Children - Oorloff, Selina; Rooney, Rosanna; Baughman, Natalie; Kane, Robert; McDevitt, Maryanne; Bryant, Aidan (Frontiers in Psychology, 2021)
Research indicates that mental health disorders can occur in children as young as four years of age, prompting the need for prevention programs for young children. The ability to use healthy strategies to cope with emotions is a protective factor against mental health disorders that can be effectively taught to children from an early age. The current study used a pre-test post-test cluster randomised controlled trial to test the efficacy of the new Aussie Optimism: I Spy Feelings Program. The aim of the study was to investigate the effects of the program on children’s emotional coping. The program included content on emotion regulation strategies, focusing on the emotions of happiness, sadness, anger, fear and worry. The participants were 73 children (intervention = 33; control = 40) from pre-primary classes. Four schools were cluster randomised to the intervention or control group, resulting in two schools in each condition. Parents completed measures of their children’s emotional coping with sadness, anger and worry. Children in the intervention group participated in ten sessions of the I Spy Feelings Program, spread over five weeks. The results indicated a significant, small to moderate intervention effect for coping with anger. Children in the control group decreased in their ability to cope with anger, while children in the intervention group remained stable. No intervention effects were found for coping with sadness or worry, with results for these emotions staying stable across time for both groups. This pilot study will inform the further development of the program. The effects of the program on coping with anger provide support for the use of emotion regulation strategies in intervention programs to maintain healthy emotional coping, which is a protective factor against internalising and externalising disorders in childhood.